A‐band structural dynamics of thioanisole by resonance Raman spectroscopy. (6th December 2012) - Liu, Ming‐Xia; Xie, Bin‐Bin; Li, Ming‐Juan; Zhao, Yan‐Ying; Pei, Ke‐Mei; Wang, Hui‐Gang; Zheng, Xuming
<x xml:space="preserve">Abstract</x> The structural dynamics of thioanisole in the S2(ππ*) electronic state that has large oscillator strength was studied by using the resonance Raman spectroscopy. The vibrational assignments were done for thioanisole on the basis of the FT‐Raman and FT‐IR measurements, the density‐functional theory computations and the normal mode analysis. The A‐ and B‐band resonance Raman spectra were obtained in cyclohexane, methanol and acetonitrile, in which ten modes in A' irreducible representations were observed. The structural dynamics were obtained according to the resonance Raman intensity pattern. The vibroinc‐coupling between the S3(πσ*) electronic state that has no oscillator strength and the S2(ππ*) electronic state were revealed. We discuss the correlation between our present structural dynamics and the previous S2(ππ*)/S3(πσ*) conical intersectional dynamics revealed by resonant‐enhanced two‐photon ionization and the photofragment excitation spectroscopic study. Copyright © 2012 John Wiley & Sons, Ltd.